STUDYING ON FREEZING POINT OF EJACULATES , VARIATION, THE EFFECT OF BULLS AGE AND ‎RELATIONSHIP BETWEEN IT AND SOME CHARACTERISTICS OF SEMEN AND FREREZABILITY - I. Al-Badry, Karem; W. Al-Dovri, Tawfiq.; H. Ali‎, Hussam (The Iraqi Journal of Veterinary Medicine, 1988)
170 ejaculates collection from "14" Friesian bulls born in Iraq to study the variation in freezing point of these ejaculates, effect of bulls age on it, the relationship between it with some semen characteristics and freezability of ejaculates. The result of this study can summarized in:Freezing point of bull semen was ranged between -0,.55 to -0.67 C, bulls age were effected on it, and point of bull semen and individual motility, mass motility and sperm concentration mld/al. but I thas significant negative correlation with hydrogen ion concentration.Freezability of ejaculates increase with more decrease in freezing point of it. The correlation between freezing point of bull semen and individual motility, survival and survival index were Bignificant positive. But the percentage of dead, abnormal head and tail spermatozoa have significant negative correlation with it